2018
DOI: 10.3389/fnbot.2018.00018
|View full text |Cite
|
Sign up to set email alerts
|

A Subject-Specific Kinematic Model to Predict Human Motion in Exoskeleton-Assisted Gait

Abstract: The relative motion between human and exoskeleton is a crucial factor that has remarkable consequences on the efficiency, reliability and safety of human-robot interaction. Unfortunately, its quantitative assessment has been largely overlooked in the literature. Here, we present a methodology that allows predicting the motion of the human joints from the knowledge of the angular motion of the exoskeleton frame. Our method combines a subject-specific skeletal model with a kinematic model of a lower limb exoskel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 22 publications
(24 reference statements)
0
18
0
Order By: Relevance
“…Although these mechanisms will add inertia and bulk to the device, undesired interaction forces and torques can be significantly reduced, with an impact on perceived comfort [18]. Overall, relative motion of interfaces should be minimized as to optimize comfort, efficiency, and reliability of exoskeletons [24].…”
Section: Introductionmentioning
confidence: 99%
“…Although these mechanisms will add inertia and bulk to the device, undesired interaction forces and torques can be significantly reduced, with an impact on perceived comfort [18]. Overall, relative motion of interfaces should be minimized as to optimize comfort, efficiency, and reliability of exoskeletons [24].…”
Section: Introductionmentioning
confidence: 99%
“…A known future gait trajectory adds a feedforward term to powered exoskeleton devices instead of predominantly relying on feedback sensors [ 1 , 27 , 29 , 69 ]. This would improve device performance by narrowing down the nonlinear kinematic differences between the user and the device and therefore avoid altering the user’s natural gait trajectories [ 70 , 71 ]. Prediction of future gait trajectory could substantially improve the design of prosthetics by adapting the device controlling parameters according to the user’s movement [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the intra-subject implementation shows better performance in both gait trajectory and gait phase prediction than inter-subject implementation, which suggests that subject-specific training is preferable if the gait trajectory and gait phase are to be used for an exoskeleton framework. Although a generic model can reduce the time required in the training process, some studies have shown that a generic model may not be suitable for specific individuals, and that subject-specific musculoskeletal geometry is essential for high prediction accuracy [ 44 , 45 ]. One advantage of our approach is that no anthropometric geometry measurements are needed in either implementation.…”
Section: Discussionmentioning
confidence: 99%